2016
DOI: 10.1186/s12864-016-3292-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of DNA that determine RNA polymerase II core promoter

Abstract: BackgroundThe general structure and action of all eukaryotic and archaeal RNA polymerases machinery have an astonishing similarity despite the diversity of core promoter sequences in different species. The goal of our work is to find common characteristics of DNA region that define it as a promoter for the RNA polymerase II (Pol II).ResultsThe profiles of a large number of physical and structural characteristics, averaged over representative sets of the Pol II minimal core promoters of the evolutionary diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 57 publications
(54 reference statements)
6
16
0
Order By: Relevance
“…Thse frequency of XY dinucleotides was calculated not in the whole genome but in the 200-bp-long genome fragment around the read-start positions. By doing that we took into account all the sequence biases associated with read mapping positions 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Thse frequency of XY dinucleotides was calculated not in the whole genome but in the 200-bp-long genome fragment around the read-start positions. By doing that we took into account all the sequence biases associated with read mapping positions 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The entwined aspect found suggests the promoter activity is well represented and each one of the energy-related features might describe promoter activity. The employment of structural features has shown a satisfactory way to locate transcription factor (TF) protein binding sites [13] in a way sheer consensual motifs are not enough to represent promoter activity, indeed, Deyneko et al [10] suggested that there is a feature conservation around promoter sequences.…”
Section: Rnap Binding Is Explained By Different Levels Of Enthalpy Free-stability and Base-pair Stackingmentioning
confidence: 99%
“…At the scale of a few nucleotides, DNA structure is determined by the arrangement of bases, the nature of which determines the depth and hydropathy of the DNA grooves, as well as local electrostatic and electronic properties which collectively determine interactions between DNA and proteins such as transcription factors recruiting RNA polymerases [26]. At the scale of a dozen to hundreds of nucleotides, the nucleotide composition determines DNA thermodynamic and mechanical properties, such as resistance and response to topological stresses with consequences on transcription initiation and elongation [25,31,247]. Nucleotide composition-dependent mechanical properties, such as DNA bendability and rigidity, play a role in nucleosome positioning.…”
Section: Appendix A1 Genome Physical Organization: From Gene Expresmentioning
confidence: 99%